2003
DOI: 10.4049/jimmunol.170.5.2557
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein-7 Inhibits Constitutive and Interleukin-1β-Induced Monocyte Chemoattractant Protein-1 Expression in Human Mesangial Cells: Role for JNK/AP-1 Pathway

Abstract: Bone morphogenetic protein-7 (BMP-7), which belongs to the TGF-β superfamily, has been shown to reduce macrophage infiltration and tissue injury in animal models of inflammatory renal disease. To explore the mechanism involved in the anti-inflammatory effect, we investigated the effect of BMP-7 on monocyte chemoattractant protein-1 (MCP-1) expression in cultured human mesangial cells. BMP- 7 significantly inhibited constitutive and IL-1β-induced MCP-1 protein production and MCP-1 mRNA expression by mesangial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 48 publications
2
26
1
Order By: Relevance
“…SP600125 here inhibited IL-1␤-or TNF-␣-induced MCP-1 expression, suggesting that JNK is required for optimal MCP-1 expression in PSCs. This is in agreement with the previous report showing that JNK was necessary for IL-1␤-induced MCP-1 expression in human mesangial cells (Lee et al, 2003). We have previously reported that ethanol and acetaldehyde at clinically relevant concentrations activated JNK, but they failed to induce MCP-1 expression in PSCs (Masamune et al, 2002b).…”
Section: Discussionsupporting
confidence: 82%
“…SP600125 here inhibited IL-1␤-or TNF-␣-induced MCP-1 expression, suggesting that JNK is required for optimal MCP-1 expression in PSCs. This is in agreement with the previous report showing that JNK was necessary for IL-1␤-induced MCP-1 expression in human mesangial cells (Lee et al, 2003). We have previously reported that ethanol and acetaldehyde at clinically relevant concentrations activated JNK, but they failed to induce MCP-1 expression in PSCs (Masamune et al, 2002b).…”
Section: Discussionsupporting
confidence: 82%
“…30 In the present study, DN-ASK and DN-p38MAPK inhibited the NF-B activities by angiotensin II and pyrrolidine dithiocarbamate inhibited MCP-1 mRNA expression by angiotensin II, thereby suggesting the important role of NF-B through ASK-1 and p38MAPK signaling on MCP-1 expression in cardiac fibroblasts. Although activation of JNK is reported to be important for MCP-1 gene expression in other type of cells, 31 angiotensin-II-induced JNK activation has no marked effects on MCP-1 expression in the present study. Because DN-p38MAPK inhibited and DN-JNK did not inhibit the activation of NF-B by angiotensin II in the present study, one of the reasons for different effects between JNK and p38MAPK on MCP-1 expression may be different NF-B activation in cardiac fibroblasts.…”
Section: Omura Et Al Ask-1 and Mcp-1 273contrasting
confidence: 75%
“…Thus, the increase in eosinophils at estrus does not appear to play a critical role in establishing uterine homeostasis. Nonetheless BMP-2 (Kim et al 1999, Willette et al 1999, BMP-4 (Cunningham et al 1992, Miyazaki et al 2003 and BMP-7 (Gould et al 2002, Lee et al 2003 have been linked to chemotaxis in a variety of cell types (including blood cells), leaving open the question of whether BMPs (in addition to IL-5 and eotaxin), might also play a role in eosinophil infiltration into the uterus. By in situ hybridization, we detected BMP-RIA and -RII in the myometrium.…”
Section: Discussionmentioning
confidence: 99%